Socio-demographic and pregnancy-related characteristics associated with prenatal distress: a Turkish study - Emel Bahadir Yilmaz (University of Ostrava, 2019)
Aim: This study aimed to determine socio-demographic and pregnancy-related characteristics associated with prenatal distress. Design: Cross-sectional study. Methods: This cross-sectional study was carried out at the obstetrics and gynecology clinics of the Maternity and Children's Hospital, Giresun, Northern Turkey (n=230). The data were collected using the Demographic Information Form, Insomnia Severity Index, and Prenatal Distress Scale. The Kruskal Wallis test and the Mann Whitney U test were used to compare characteristics. Bivariate correlation analysis was conducted to investigate the influencing factors of prenatal distress. Results: Prenatal distress levels of pregnant women were low (10.27 ± 5.02). Prenatal distress was affected at the level of statistical significance by employment status (Z = -1.976; p = 0.048), income status (X2 = 6.568; p = 0.037), and history of stillbirth (Z = -2.398; p = 0.016). Nausea, vomiting, and insomnia during pregnancy were determined as significant variables that increase prenatal distress level. Conclusion: The results for this Turkish population were consistent with the previous literature on prenatal distress and influencing factors of pregnant women. Evaluation of prenatal distress level in pregnancy follow-up is necessary to prevent the development of mental illness. In this respect, it is suggested that pregnancy follow-up be carried out with a holistic approach.